Making Teachers and School Health Nurses Part of Pediatric Diabetes Teams - Şükrü Hatun; Gül Yeşiltepe Mutlu; Gülcan Kılınç; Zehra Aycan (JCRPE)
Children with diabetes need consistent care across all environments, including school, where they spend significant time. Türkiye’s Diabetes at School Program, initiated in 2010, has made substantial progress in integrating diabetes care into the school system. The program’s achievements include government support, annual awareness activities, communication between diabetes teams and schools, policy implementation, and training for school staff. A recent meeting of Provincial Health Service Officers highlighted ongoing efforts and future directions for the program, emphasizing the importance of continuous support for children with diabetes in educational settings. Key outcomes of this meeting included designated caregivers for children with diabetes at school, optional administration of insulin by trained staff, mandatory diabetes education for teachers, and health-conscious policies for school activities. The program’s success is attributed to the collaborative efforts of teachers, healthcare professionals, and government officials. Ensuring robust support for children with diabetes in schools is vital for their well-being and academic success.